2020
DOI: 10.1097/md.0000000000021587
|View full text |Cite
|
Sign up to set email alerts
|

Acupotomy combined with massage for cervical spondylotic radiculopathy

Abstract: Background: Cervical spondylotic radiculopathy (CSR) is a clinical syndrome of radial neck and shoulder pain. Both Massage and Acupotomy have been widely used in the treatment of CSR, in China and achieved satisfied efficacy. Therefore, the aim of this study is to systematically evaluate the clinical efficacy of acupotomy combined with massage in the treatment of CSR. Methods: The following electronic databases will be searched: PubMed, Web of Science, the Cochrane Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…After CS occurrence, the muscles behind the cervical spine remain in a tense state for a prolonged time, and the surrounding tendons form hard knots or inflammatory adhesions. These reaction points further increase the stress on the cervical intervertebral disc and accelerate its degeneration [48][49][50]. Therefore, we selected the tendon node around the cervical spine as the Ns intervention point.…”
Section: Discussionmentioning
confidence: 99%
“…After CS occurrence, the muscles behind the cervical spine remain in a tense state for a prolonged time, and the surrounding tendons form hard knots or inflammatory adhesions. These reaction points further increase the stress on the cervical intervertebral disc and accelerate its degeneration [48][49][50]. Therefore, we selected the tendon node around the cervical spine as the Ns intervention point.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of economy and safety risks, conservative treatment is usually the first choice for patients. At the early stage of CSR, it is widely recommended that conservative treatment is performed for six to 12 weeks, and that surgical treatment should be considered if symptoms do not improve significantly [ 1 , 6 , 7 ]. According to statistics, only 10–25% of CSR patients ultimately need surgical treatment, with the rest achieving satisfactory results through conservative treatment [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, CR treatment involves surgical intervention, such as anterior cervical decompression and fusion, cervical disc replacement, and posterior foraminotomy, and nonsurgical intervention. All CR patients should be treated with strict conservative treatment for at least 6 weeks unless the occurrence of myelopathy or severe muscle weakness or no improvement after 6 to 12 weeks of nonsurgical intervention [ 4 ]. Numerous studies have indicated that nonsurgical treatment, consisting of anti-inflammatory drugs, physical therapy, cervical traction, epidural steroid injections, exercise, massage, acupuncture, etc., has been commonly used as an optimal scheme for most CR patients [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%